2022
DOI: 10.1111/ijd.16029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social determinants of health on hospital patient outcomes in cutaneous lupus erythematosus

Abstract: report in conjunction with wound care and oral antibiotics. Suction may represent a less invasive and less painful alternative to surgical debridement. 1 Occlusive agents cause asphyxiation and emergence of maggots, allowing for subsequent mechanical removal. Ether followed by normal saline irrigation was described in one case report; there were no side effects reported and no evidence of local or systemic infection nor recurrence of maggots. 4 Turpentine oil was described in a similar fashion, but this treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Finally, socioeconomic factors like reduced income and low educational attainment have been associated with worse outcomes in patients with CLE ( 7 , 15 , 19 , 23 , 26 , 30 , 33 , 35 ). A diagnosis of CLE comes with significant financial burden.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, socioeconomic factors like reduced income and low educational attainment have been associated with worse outcomes in patients with CLE ( 7 , 15 , 19 , 23 , 26 , 30 , 33 , 35 ). A diagnosis of CLE comes with significant financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…The exception to this finding comes from a predominately White population study in Minnesota which found the prevalence of CLE to be higher than SLE in men than in women (11). All studies investigating alterations in disease course or severity were predominately female cohorts (16)(17)(18)(19)(20)(21)25). Gender did not play a significant role in predicting progression of disease activity in a multicenter endeavor studying the natural disease course of CLE (21).…”
Section: Gendermentioning
confidence: 96%
See 3 more Smart Citations